Applications in multicriteria decision making, data envelopment analysis, and finance - Lawrence, Kenneth D.; Kleinman, Gary. (Bingley, U.K. : Emerald, 2010)
'Applications of Management Science' is a blind refereed serial publication published on an annual basis. The objective of this research annual is to present state-of-the-art studies in the application of management science to the solution of significant managerial decision-making problems. It significantly aids the dissemination of actual applications of management science in both the public and the private sectors. Volume 14 is directed toward the application of management science to multi-criteria decision making, Data Envelopment Analysis (DEA) and financial performance analyses. This volume is arranged in three sections. The first section focuses on multi-criteria decision making; the second focus is on the application of DEA to public schools, paper mills, nursing home quality, retailing, health care services, and performance efficiencies in cities. The third section focuses on multi-dimensional performance of a national stock market and the effect of organizational structure on micro-financial institutions. This volume will prove to be most valuable to those interested in financial performance measurements, productivity measurement and analysis, and management science, both as practitioners and researchers.
Selected multiobjective methods for multiperiod portfolio optimization by mixed integer programming / Bartosz Sawik -- An integrated multiobjective model for two-dimensional warranty policies / Amitava Mitra, Jayprakash G. Patankar -- Selecting board of directors for socially responsible firms using a multicriteria decision model / Elizabeth Cooper, Karen M. Hogan, Gerard T. Olson -- Data envelopment analysis is not multiobjective analysis / Ronald K. Klimberg, Kenneth D. Lawrence, Sheila M. Lawrence -- Multiple criteria DEA with and without weighting restrictions / Robert Stawicki, Kenneth D. Lawrence -- A multicriteria approach to critical facility security system design / Patrick T. Hester, Sankaran Mahadevan -- Performance comparisons of Missouri public schools using data envelopment analysis / Walter A. Garrett, N.K. Kwak -- DEA studies on comprehensive efficiency of output allocation with an application to paper mills along the Huai River / Feng Yang, Yanfang Yuan, Liang Liang, Zhimin Huang -- An optimized DEA-based financial strength indicator of stock returns for U.S. markets / N.C.P. Edirisinghe, Xin Zhang -- Managing nursing home quality using DEA with weight restrictions / Daniel G. Shimshak -- Benchmarking large U.S. retailers using a data envelopment analysis model / Rashmi Malhotra, D.K. Malhotra, C. Andrew Lafond -- Using DEA to assess the efficiency of public health units in providing health care services / Rouselle F. Lavado, Leizel P. Lagrada, Brian C. Gozun -- Performance improvement on cross-efficiencies and applications to competitive advantages of Chinese cities / Yong Zha, Liang Liang, Jie Wu, Zhimin Huang -- Multidimensional performance of listed companies at the Philippine stock exchange / Florence P. Bogacia, Emilyn Cabanda -- The impact of the organizational structure on the performance of microfinance institutions using data envelopment analysis / Komlan Sedzro, Mariam Keita, Tov Assogbavi.
Keywords: Business enterprises -- Finance -- Decision making; Data envelopment analysis; Multiple criteria decision making